Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS

Preparation and characterization of self-photostabilizing UV-durable bionanocomposite membranes for outdoor applications - Kushwaha, Omkar S.; Avadhani, C. V.; Singh, R. P. (Carbohydrate Polymers, 2015)
Here, we report a durable and ultraviolet (UV) resistant nanocomposite membrane of chitosan (CS) with effective photostabilization ascribed to Zinc oxide (ZnO) nanoparticles. Zinc oxide nanoparticles were successfully dispersed in the solution of chitosan polymer. The nanocomposite films with the homogenous dispersion of ZnO nanoparticles in the chitosan matrix were obtained by solution casting method and the influence of ZnO nanoparticles as a photostabilizer was studied. The nanocomposite membranes were photoirradiated by polychromatic radiations with lambda > 300 nm using mercury vapour lamps in SEPAP instrument. The resulting nanocomposite material exhibited excellent UV-resistance in very low percentages of ZnO nanoparticles. The chitosan membranes showed fast degradation attributes than the nanocomposite membranes. ZnO nanoparticles effectively absorbed UV radiations, thus protecting polymer from radiation degradation. The neat and irradiated nanocomposites of chitosan and ZnO nanoparticles (CS/ZnO) were characterized by Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy for the chemical changes/degradation taking place. Chitosan nanocomposites were further characterized for tensile properties, contact angle measurements and surface morphology. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bionanocomposite membrane; Chitosan; Contact angle measurement; Fourier transform infrared spectroscopy; Photostabilization; Zinc oxide nanoparticles